Penerapan LKPD Model Pembelajaran Inkuiri Terbimbing sebagai Penguatan Keterampilan Proses Sains Siswa Kelas X DKV 1 SMK Muhammadiyah 2 Pekanbaru - Muliana Fransiska; Qonaah Nuryan Arif (Jurnal Pendidikan Dirgantara, 2025)
This article provides an explanation of how the use of LKPD using the guided inquiry learning model to train the science process skills of class X students at SMK Muhammadiyah 2 Pekanbaru. By using guided inquiry LKPD, it allows students to learn actively and be able to practice their science process skills. Students can improve their ability to observe, interpret observations, predict, apply concepts, communicate and ask questions. These are indicators that can be trained in science process skills. Data were collected through several techniques, including literature review and classroom observation. All data obtained in this article are based on the results of literature reviews and observations that have been made at SMK Muhammadiyah 2 Pekanbaru. The use of Guided Inquiry LKPD is expected to train students' science process skills, especially in science learning. The findings of this research include; lack of supporting learning media, such as infocus and speakers and inadequate networks that disrupt the learning process. The results showed that students' science process skills were well trained.